In search of self: Navigating subjectivity amidst conflicts in Rainbow Rowell’s Eleanor & Park (2012) - Azalea Ayu Dewinta Fitriani; Isti Siti Saleha Gandana; Nia Nafisah (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2021)
Entrance into adulthood has often been seen as a phase marked by self-exploration, instability, and struggles to overcome tensions and conflicts. Eleanor & Park (2012) is a novel that explores issues of growing up and tells the story of how the two main characters go through the struggles of their adolescent lives. This study analyzes how Eleanor and Park construct and navigate their subjectivities amidst the various conflicts they face. It does so by, first, identifying and classifying the conflicts the characters encounter and then locating their provisional subject positions that draw on how they react to and deal with the conflicts. While the study confirms the dynamic nature of subject positions, both Eleanor and Park tend to bring to the fore their active subject position in dealing with the conflicts. Moreover, their subject positions further indicate that Eleanor and Park are empowered agents who are capable of deliberating thoughts and actions consciously. In navigating their subjectivities, both characters, in the end, are able to achieve personal growth and empowerment.